Characteristics Study of Raft Houses in the Musi River of Palembang - Anta Sastika; Raden Ahmad Nur Ali; Cito Pringga Yudha (Jurnal Arsitektur, 2023)
Palembang is one of the cities in Indonesia which has a large river, namely the Musi River. The Musi River divides the city of Palembang into two parts, namely across the Ulu and across the Ilir. The life of the people of Palembang has been very close to the river where many life activities take place in the river. Along the river there are many traditional settlements, one of which is a raft house we called is rumah rakit. The beginning of the appearance of the raft house is inseparable from the political history in the Palembang, where at that time foreigners who came to the Palembang were not allowed to have a place to live on the mainland, so many immigrants built houses on the river. But now the existence of raft houses is starting to be abandoned along with changes in the government system where everyone can own and build a house on the mainland. The characteristics of buildings above the river certainly have significant differences when compared to buildings built on land, so it is necessary to conduct an in-depth study of raft houses. This study aims to determine the characteristics of the raft house in terms of architecture, structure, building materials and utility systems. To find the characteristics of the raft house, this research was conducted through a descriptive-analytic qualitative research method approach, namely analyzing each component of the raft building. The results obtained in the study indicate that the design of the raft house is an adaptive result to the geographical conditions of the Musi river and is different from existing buildings on the mainland.